Calculation Method of Aerodynamic Performance of Small Propeller with Serrated Trailing Edge. (July 2020) - Lan, Tian; Li, Guoxi; Zhang, Meng
Abstract: The small propeller with serrated trailing edge of the UAV has the characteristics of low aerodynamic noise. In this paper, based on the momentum-leaf theory and modified the airfoil parameters, the aerodynamic performance calculation method of the propeller with a serrated tail structure is put forward. Combined with the CDF technology of three-dimensional aerodynamic performance analysis of small propeller blades at low Reynolds number, this method was used to calculate the aerodynamic performance of the small propeller with serrated tail structure, and the calculation results were experimentally verified. The experimental results show that, using the modified airfoil parameters, the established aerodynamic performance calculation method of the tail serrated structure propeller hover state has a good effect.